Role of the renin–angiotensin system in the pathophysiology of coronary heart disease and heart failure: Diagnostic biomarkers and therapy with drugs and natural products - Mehta, Jinit K.; Kaur, Ginpreet; Buttar, Harpal S.; Bagabir, Hala Abubaker; Bagabir, Rania Abubaker; Bagabir, Sali Abubaker; Haque, Shafiul; Tuli, Hardeep S.; Telessy, Istvan G. (Frontiers in Physiology, 2023)
The renin–angiotensin system (RAS) plays a pivotal role in blood pressure regulation. In some cases, this steering mechanism is affected by various deleterious factors (mainly via the overactivation of the RAS) causing cardiovascular damage, including coronary heart disease (CHD) that can ultimately lead to chronic heart failure (CHF). This not only causes cardiovascular disability and absenteeism from work but also imposes significant healthcare costs globally. The incidence of cardiovascular diseases has escalated exponentially over the years with the major outcome in the form of CHD, stroke, and CHF. The involvement of the RAS in various diseases has been extensively researched with significant limelight on CHD. The RAS may trigger a cascade of events that lead to atherosclerotic mayhem, which causes CHD and related aggravation by damaging the endothelial lining of blood vessels via various inflammatory and oxidative stress pathways. Although there are various diagnostic tests and treatments available in the market, there is a constant need for the development of procedures and therapeutic strategies that increase patient compliance and reduce the associated side effects. This review highlights the advances in the diagnostic and treatment domains for CHD, which would help in subjugating the side effects caused by conventional therapy.